Production of Electricity Through Pressure Based Sensors - Divyakumar, N; Ganesh, VS; Vishnuraju, G; Yogesh, P; Sangappa, SB (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we generate power through pressure based sensor. Proposal for the utilization of waste energy of foot power with human locomotion is very much relevant and important for highly populated countries like India and China where the roads, railway stations, bus stands, temples, etc. are all over crowded and millions of people move around the clock. This whole human/ bio energy being wasted if it can be made possible for utilization it will be great invention and crowd energy farms will be very useful energy sources in crowded countries In this project we are generating electrical power as non-conventional method by simply walking or running on the foot step. Non-conventional energy system is very essential at this time to our nation. Non-conventional energy using foot step is converting mechanical energy into the electrical energy. Power generation using conservative method becoming deficient. There is a necessity arises for a different power generation method. At the same time the energy is was due to human locomotion and many ways. To overcome this problem, the energy wastage can be converted to usable form using the Piezoelectric sensor. This sensor converts the pressure on it to a voltage. So by using this energy saving method, that is the Footstep Power Generation System we are generating power.